ANALISIS COMPENSABLE FACTORS DAN PERBANDINGAN TERHADAP KEBIJAKAN UPAH MINIMUM PADA SISTEM KOMPENSASI KARYAWAN USAHA KECIL MENENGAH - Lindawati Kartika; Silvy Mutiara; Irani Bening Kinasih; Muhammad Muzakkir R; Ayu Novitasari (JABE (Journal of Applied Business and Economic), 2022)
SMEs play a big role in the Indonesian economy, which contributes to 61.97% of GDP in 2020. Employees are the most important asset for a company, so companies should provide proper compensation. This also applies to SMEs in the trade sector. Therefore, it is necessary to evaluate the SME compensation system based on compensable factors. The purpose of this research is to assess the compensation system for the UMP and UMK, to examine the job qualifications required for each position, and to examine the compensable factors in the trade sector SMEs. The research method uses descriptive analysis through the Hay Method approach with a sample of six SMEs from Bogor, Depok, Lampung, Bali, and Lombok. The secondary data sources were obtained from the results of the employee salary survey research and literature study. The results show that there are still many SMEs that have not set a compensation system according to the UMP and UMK. The highest job qualifications are in manager positions, while the lowest job qualifications are in staff positions. Meanwhile, there are ten compensable factors that are most often used in determining the amount of compensation for SME employees in the trade sector, including education, experience, customer service orientation, physical effort, responsibility, communication, analysis and problem solving, planning and coordination, freedom of action, and working conditions. It is hoped that the ten compensable factors can be used as a reference in determining the appropriate compensation system for SMEs in the trading sector in Indonesia.